PENGARUH MINAT BACA CERPEN TERHADAP KETERAMPILAN MENULIS CERPEN SISWA KELAS X MAN 1 PADANG - Febrina, Liga (Menara Ilmu, 2017)
This research is form the background of several phenomenon. lack of encouragement from the teacher or the surrounding environment on the importance of reading. Starting from those phenomenons, this study aims to determine the contribution of reading interestshort story to the student’s short story. The method that is used in this research is correlation analisys. The population is students of grade MAN 1 Padang. There are 103 students there. Sampling of this study was done by using simple random sampling, which resulted in sample of 50 students. Through these data sources the data obtained for the three variables studied. Data were collected using a questionnaire and tests that has been tested the validity and reliability. Furthermore, the data processed by the product moment correlation, multiple correlation, F test, and multiple regression testing to determine the contribution among those variables that being studied. Based on this research, the calculated level of understanding of respondents to a variable interest in short story was 70% with more than enough categories, while the contribution of writing short story skills by 24.80%. So, overall reading interest short story to the student’s ability at Grade X MAN 1 Padang.